THE EFFECT OF OIL PALM PRODUCTIVITY ON THE GROSS REGIONAL DOMESTIC PRODUCT IN WEST KALIMANTAN PROVINCE - Nur'aina Uswatun Khasanah; Adi Suyatno; Maswadi Maswadi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
The agriculture, forestry, and fisheries sector is the sector with the largest distribution of West Kalimantan's GRDP in 2023. West Kalimantan is the province with the third largest area of palm oil plantations in Indonesia which continues to increase every year along with the amount of production. This also affects the increase in palm oil productivity. Palm oil is the leading plantation commodity for the people of West Kalimantan which has the highest area and production compared to other plantation commodities. This study was conducted to analyze the effect of palm oil productivity on the economy in West Kalimantan Province through the Gross Regional Domestic Product (GRDP). Panel data regression is the method used in this study with the best selected model being the Random Effect Model (REM). The Central Statistics Agency and the Provincial Plantation and Livestock Service are agencies as sources for obtaining secondary data used in this study. Time series data in the form of 12 years of data used starting from 2011 to 2022 from 13 Regencies/Cities in West Kalimantan as cross-section data. This study provides results that palm oil productivity has a positive and significant impact on the Gross Regional Domestic Product (GRDP) in the Agriculture, Forestry and Fisheries sectors of West Kalimantan Province.